Reflections on the development and construction of space-ground integration information network - Wei WU; Peng QIN; Xu FENG; Haijiao LIU; Zhaoxiang HUANG (Dianxin kexue)
When maintaining and expanding national interests,our country’s information network has always been faced with the problem of “covering beyond its control,incompatible with information,slow in response to services and having security risks”.Building a space-ground integration information network is an effective way to deal with the challenges.Based on this,the status quo and trend of the development of the integrated world-wide information network system at home and abroad were analyzed.The concept,key technologies and implementation strategies of a global integration of information network architecture were given.